From context to concept: history and strategic environment for NATO's 2022 strategic concept. Issue 3 (3rd July 2022) - Becker, Jordan; Duda, Michael; Lute, Douglas
ABSTRACT: This article introduces ten essays capturing ten panel discussions held by the Department of Social Sciences at the United States Military Academy on 3-4 February 2022, in support of the drafting of NATO's 2022 Strategic Concept. While the shadow of the Russo-Ukrainian war hung heavy over the proceedings, participants sought to take both a long and a broad view, contemplating NATO's role in a changing international order. NATO allies must assimilate these changes into their collective and national strategies, but they are first and foremost agents themselves, whose strategies can and should shape the future. The participants asked challenging questions about what international order(s) might look like in the proximate future, and how NATO allies could shape that proximate future. The authors of this introductory essay contend that while simultaneous competition with China and Russia will be a (perhaps the) central feature of the international security landscape for years to come, the act of competing does not a Strategic Concept make. Allies must grapple with interrelated issues ranging from the evergreen question of transatlantic burden-sharing to the assimilation of emerging technologies into strategic and operational planning. The transatlantic security architecture anchored by NATO will have to be incorporated into a broader, global security network to manage competition with China and Russia while holding fast to the democratic values that are at NATO's heart.